PENATAAN JENIS TANAMAN BERBASIS HOME GARDEN UNTUK MENDUKUNG KELESTARIAN SUMBER PAKAN TRIGONA DI DESA BUKIT JANGKRIK - I Putu Eka Indrawan; Ayu Aprilyana Kusuma Dewi (Sewagati, 2024)
The Trigona honey bee farming business has rapidly developed in Bukit Jangkrik Village due to its simple cultivation and maintenance techniques. The success of this cultivation heavily depends on the availability of feed sources throughout the year, which are generally obtained from home garden-based yards. Unfortunately, the community's knowledge about the types of nectar, pollen, and resin-producing plants as food sources is still lacking, so their feeding needs have not yet been met. In order to support the sustainability of Trigona's food sources, PGRI Mahadewa University Indonesia is conducting community service activities by creating a demonstration plot of an agroforestry-based home garden model. This model combines annual fruit-bearing plants such as Durian, Matoa, Kelengkeng, Mangga, Murbei, Jeruk, Anggur, and Jambu biji, with flowering plants that produce nectar, pollen, and resin throughout the season, such as Matahari, Air Mata Pengantin, Asoka, and Kastuba. The results of the activities show the success of this demonstration plot in providing a sustainable food source, thanks to the strategic and potential arrangement of plant types. In conclusion, this agroforestry-based home garden model serves as a practical solution that not only supports the sustainability of Trigona bee cultivation but also involves the community in maintaining the local ecosystem through the planting of multifunctional plants.